Faktor yang Berhubungan dengan Keluhan Heat Strain pada Pekerja Overhaul Tangki di PT. X Kota Balikpapan - Chilwindwi, Bratarini Hassya; Ramdan, Iwan Muhamad; Hardianti, Dewi Novita; Sultan, Muhammad; Lestari, Ida Ayu Indira Dwika (UI Scholars Hub, 2025)
Heat strain is a physiological reaction of the body that functions to release excess heat through sweat output, increased body temperature, heart rate, blood pressure, and weight loss. PT X is a company that operates in the oil and gas sector. The results of the study found that the workload was not appropriate and the incidence of work accidents that occurred due to fatigue. This study was conducted to see the heat strain complaints experienced by tank overhaul workers in the Oil Refinery Area of PT. X Balikpapan City and the associated factors. This research applied quantitative method with analytical approach and cross-sectional design and the research sample amounted to 80 workers (total sampling). The results showed that heat strain complaints among tank overhaul workers at PT X Balikpapan City are included in the danger zone as many as 39 workers (48.8%). It is concluded that heat strain complaints among workers fall into the danger zone or red zone, there is a relationship between drinking water consumption (r=0.030), physical workload (r=0.039), indoor work climate (r=0.001), and outdoor work climate (r=0.018) with heat strain complaints, and there is no relationship between age (r=0.145) and length of work (r=0.539) with heat strain complaints. The company is advised to provide education on the importance of consuming drinking water to all workers, adjust the amount of work or workload according to the ability of workers, and carry out engineering controls by installing vents.